Relining of removable dentures: a literature review - Cinthia Sawamura Kubo¹; Fabrício Reskalla Amaral; Edson Alves de Campos (Revista Sul-Brasileira de Odontologia, 2015)
The alveolar bone resorption that occurs after tooth loss leads to maladaptation of prostheses over the mucosa, causing discomfort to the patient. However, these maladaptations can be solved by prosthesis relining. Objective: The aim of this study was to discuss based on the literature, the relining of complete and partial removable dentures. Literature review: Dentistry makes use of relining materials that can be either rigid or resilient, having a temporary or permanent characteristic. However, to obtain a satisfactory result, the knowledge of their indications, contraindications, advantages, disadvantages is required, in addition to the characteristics and types of materials. Patients should be aware of the importance of constant monitoring, or even the need to reline their dentures, as it is not possible to determine the biological tolerance of each individual. Conclusion: The installation and proservation phases become essential to minimize bone resorption, and also to achieve rehabilitative treatment success.